Soil Subsidence in the Everglades Agricultural Area - Alan L. Wright; George H. Snyder (EDIS)
SL311, a 3-page illustrated fact sheet by Alan L. Wright and George H. Snyder, describes the soils in the agricultural region in Florida south of Lake Okeechobee growing primarily sugarcane and winter vegetables, and addresses how the soils are changing with time. Includes additional sources of information. Published by the UF Department of Soil and Water Science, November 2009.